Comparing practice and outcome of laparoscopic liver resection between high-volume expert centres and nationwide low-to-medium volume centres. Issue 8 (1st July 2021) - Görgec, B; Fichtinger, R S; Ratti, F; Aghayan, D; Van der Poel, M J; Al-Jarrah, R; Armstrong, T; Cipriani, F; Fretland, Å A; Suhool, A; Bemelmans, M; Bosscha, K; et al.
Abstract: Background: Based on excellent outcomes from high-volume centres, laparoscopic liver resection is increasingly being adopted into nationwide practice which typically includes low-medium volume centres. It is unknown how the use and outcome of laparoscopic liver resection compare between high-volume centres and low-medium volume centres. This study aimed to compare use and outcome of laparoscopic liver resection in three leading European high-volume centres and nationwide practice in the Netherlands. Method: An international, retrospective multicentre cohort study including data from three European high-volume centres (Oslo, Southampton and Milan) and all 20 centres in the Netherlands performing laparoscopic liver resection (low-medium volume practice) from January 2011 to December 2016. A high-volume centre is defined as a centre performing >50 laparoscopic liver resections per year. Patients were retrospectively stratified into low, moderate- and high-risk Southampton difficulty score groups. Results: A total of 2425 patients were included (1540 high-volume; 885 low-medium volume). The median annual proportion of laparoscopic liver resection was 42.9 per cent in high-volume centres and 7.2 per cent in low-medium volume centres. Patients in the high-volume centres had a lower conversion rate (7.4 versus 13.1 per cent; P  <   0.001) with less intraoperative incidents (9.3 versus 14.6 per cent; P  =   0.002) as compared to low-medium volume centres. Whereas postoperative morbidity and mortality rates were similar in the two groups, a lower reintervention rate (5.1 versus 7.2 per cent; P  =   0.034) and a shorter postoperative hospital stay (3 versus 5 days; P  <   0.001) were observed in the high-volume centres as compared to the low-medium volume centres. In each Southampton difficulty score group, the conversion rate was lower and hospital stay shorter in high-volume centres. The rate of intraoperative incidents did not differ in the low-risk group, whilst in the moderate-risk and high-risk groups this rate was lower in high-volume centres (absolute difference 6.7 and 14.2 per cent; all P  <   0.004). Conclusion: High-volume expert centres had a sixfold higher use of laparoscopic liver resection, less conversions, and shorter hospital stay, as compared to a nationwide low-medium volume practice. Stratification into Southampton difficulty score risk groups identified some differences but largely outcomes appeared better for high-volume centres in each risk group. Abstract : High-volume expert centres had a sixfold higher use of laparoscopic liver resection, less conversions, and shorter hospital stay, as compared to a nationwide low-medium volume practice. Stratification into Southampton difficulty score risk groups identified some differences but largely outcomes appeared better for high-volume centres in each risk group.